The prognostic and predictive value of homologous recombination deficiency status in patients with advanced stage epithelial ovarian carcinoma after first-line platinum-based chemotherapy - Xu, Yiqing; Chen, Yi-Ju Amy; Wu, Yunhong; Saverimuthu, Angela; Jadhav, Archana; Bhuiyan, Rehana; Sandler, Jason; Yio, Jiang; Kumar, Vivek (Frontiers in Oncology, 2024)
Objective Homologous recombination (HR) comprises series of interrelated pathways that repair double-stranded DNA breaks and inter-strand crosslinks. It provides support for DNA replication to recover stalled or broken replication forks. Compared with homologous recombination proficiency (HRP), cancers with homologous recombination deficiency (HRD) are more likely to undergo cell death when treated with DNA-damaging agents, such as platinum agents, and have better disease control. Methods Patients diagnosed with stage III/IV ovarian cancer, early stages with recurrence, who received adjuvant chemotherapy after debulking surgery, and who also had known HR status were eligible. Results Forty-four patients were included, with 21 in the HRD group (including 8 with germline mutations) and 23 in the HRP group. The HRD group was composed predominantly of serous carcinoma (95.2%), while mucinous (n=3) and clear cell (n=1) cases were all found in the HRP group. Stage III/IV disease was 66.7% and 91.3% in HRD and HRP groups, respectively (p=0.064). Patients who were optimally debulked to no residual disease was 90.0% and 72.7% (p=0.243), respectively. Late line use of PARP inhibitors was 33.3% and 17.4% (p=0.303). Median PFS was 22.5 months (95% CI, 18.5 - 66.6) and 21.5 months (95% CI, 18.3-39.5) (p=0.49) in HRD and HRP respectively. Median platinum free interval (PFI) was 15.8 months (95% CI 12.4-60.4) and 15.9 months (95% CI 8.3-34.1) (p=0.24), respectively. Median OS was 88.2 months (95% CI 71.2-NA) and 49.7 months (95% CI 35.1-NA) (p=0.21). The PFS of the patients with germline BRCA mutations (n=5) was 54.3 months (95% CI 23.1-NA) and 21.5 months (95% CI 18.3-39.5) in the HRP group (p=0.095); the PFI difference was 47.7 months (95% CI 17.6-NA) in the BRCA mutation group, and 15.9 months (95% CI 12.4-60.4) in HRP, showing statistical significance (p=0.039); while the median OS was NA and 49.7 months (95% CI 35.1-NA) respectively (p=0.051). When adding two additional patients with somatic BRCA mutations to the germline BRCA mutation carriers, the median OS is NA (95% CI 73, NA) versus 49.7 months (95% CI 35.1, NA) for HRP (p=0.045). Conclusions HRD status was not associated with longer PFS or PFI in advanced ovarian cancer who received first line adjuvant platinum-based chemotherapy. Its role as a prognostic marker for overall survival is suggested, particularly in the subgroup with germline and somatic BRCA mutations.